Application of the national early warning score (NEWS) in patients with acute aortic dissection: A case–control study. Issue 11 (29th August 2021) - Liu, Yuwen; Li, Qingyin; Zhang, Yanjuan; Zhao, Rui; Pang, Ran; Ren, Hua
Abstract: Background: The vital‐sign monitoring strategy of patients with acute aortic dissection in the emergency department is mainly based on traditional experience. This study attempts to explore the significance of the national early warning score (NEWS) in monitoring the condition of patients with acute aortic dissection during emergency observation and to provide evidence for emergency nurses in optimal and scientific monitoring of patients. Methods: The case–control method was used to continuously enrol patients with acute aortic dissection who had been in the emergency department; the STROBE checklist was used in this process. Based on patients' clinical deterioration, they were divided into two groups: clinical deterioration and non‐clinical deterioration. The NEWS at each time point was compared by independent‐samples t‐test, and the predictive power of NEWS was evaluated according to the area under the receiver operating characteristic curve. Results: A total of 290 patients with acute aortic dissection were included: 46 patients showed clinical deterioration and 244 did not. There were significant differences in the NEW scores of the two groups at admission time and at 12, 8, 4 and 0.5 h before clinical deterioration. The NEW scores of the clinical deterioration group showed an upward trend, while the non‐clinical deterioration group showed a relatively stable trend. The NEWS can be used to predict the occurrence of clinical deterioration earlier at 4 h before clinical deterioration. Simultaneously, the patient's respiration rate and SpO2 had better predictive performance than other vital signs. Conclusion: The NEWS can be used to triage patients with acute aortic dissection admitted to the emergency department. Continuous use of the NEWS for monitoring can play a vital role in early warning of clinical deterioration in patients with acute aortic dissection. In clinical care, attention should also be paid when patients with acute aortic dissection have abnormal respiration rate and SpO2 .